Perceived Sensations in Architectural Spaces through Immersive Virtual Reality - Hugo C. Gomez-Tone; Jorge Martin-Gutierrez; John Bustamante-Escapa; Paola Bustamante-Escapa; Betty K. Valencia-Anci (Vitruvio: International Journal of Architectural Technology and Sustainability)
To design architectural spaces that not only respond to the basic needs of users, but also seek their emotional well-being, it is necessary for the architecture students to have a special sensitivity and be aware of the different sensations that their designs should and can evoke. To achieve this competence without exploring real spaces, Immersive Virtual Reality technology offers an important contribution to the field of architecture. The purpose of this research is to determine if the sensations perceived in virtual architectural spaces by students are similar to the real ones and to determine the characteristics of this technology that allow a better perception of sensations. Six architectural modules were designed to be walked through and experienced at real scale using a Head Mounted Display by 22 students of the first and fifth year of studies of Architecture career in Peru. An ad-hoc questionnaire allowed to know the perceived sensations and the benefits of the tool. The results obtained showed that the perception of sensations of the fifth year students is a little closer to those expressed by a group of seven experts compared to that of the first year students and that the students consider the characteristics of accessibility, real scale of the space and the possibility of going through and looking at the space in all directions are those that have given more realism to the experience and therefore better perception of the space, while the characteristics of natural light and shadows, construction materials and external environment have been less valued in the realism of the experience. It is concluded that the sensory experimentation in architectural spaces modelled realistically in virtual environments allows the perception of sensations very similar to those that the architect seeks to convey initially.